2017
DOI: 10.1016/j.anireprosci.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Single Layer Centrifugation Porcicoll (70%, 80% and 90%) or supplementation with reduced glutathione, seminal plasma and bovine serum albumin on frozen-thawed boar sperm

Abstract: Selecting the optimal sperm population is essential for success with reproductive techniques. Porcicoll (formerly Androcoll-P) is a colloid formulation for selection of high-quality boar spermatozoa by single layer centrifugation (SLC). To date, most studies have been carried out with fresh semen and large volumes. We carried out 2 experiments to test the use of Porcicoll for thawed boar semen in small volumes. In Experiment 1, cryopreserved semen doses were thawed, split in 200-μL aliquots and layered on 1mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In rams, Šterbenc et al [ 14 ] observed that centrifugation of frozen/thawed semen with a species-specific colloid (Androcoll-O) increases the proportions of spermatozoa with an intact plasma membrane and DNA, and of motile spermatozoa. In pigs, SLC with Porcicoll (formerly known as Androcoll-P) has been found to enhance the quality of frozen/thawed sperm, in terms of viability, mitochondrial activity and intracellular levels of ROS [ 15 ]. Also in pigs, centrifugation of semen with SLC with Porcicoll prior to cryopreservation increases the cryotolerance and fertilizing ability of frozen/thawed sperm [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rams, Šterbenc et al [ 14 ] observed that centrifugation of frozen/thawed semen with a species-specific colloid (Androcoll-O) increases the proportions of spermatozoa with an intact plasma membrane and DNA, and of motile spermatozoa. In pigs, SLC with Porcicoll (formerly known as Androcoll-P) has been found to enhance the quality of frozen/thawed sperm, in terms of viability, mitochondrial activity and intracellular levels of ROS [ 15 ]. Also in pigs, centrifugation of semen with SLC with Porcicoll prior to cryopreservation increases the cryotolerance and fertilizing ability of frozen/thawed sperm [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, however, no study with fresh donkey semen has been performed nor has any evaluated the effects of SLC with Equicoll on mitochondrial activity, and intracellular levels of ROS and calcium. Other studies in rams [ 14 ], pigs [ 15 ], bulls [ 16 ], and brown bears [ 17 , 18 ] have demonstrated that centrifugation with SLC increases the proportions of spermatozoa with an intact plasma membrane and acrosome, high mitochondrial activity, an intact DNA, and progressive motility, and has also been found to increase sperm cryotolerance when performed before cryopreservation [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data were clustered to obtain subpopulations (Ledesma et al., ). Flow cytometry (CyAn ADP; Beckman Coulter) yielded viability, apoptosis, capacitation, mitochondrial activity and free radicals (Crespo‐Félez et al., ). Samples were stained (Thermo Fisher) for 15 min at 37°C with probes at: 4.5 μM Hoechst 33342 and 33258, 100 nM YO‑PRO‑1, 1.5 μM propidium iodide, 1 μg/ml PNA‐FITC, 5 μM H 2 DCFDA, 1 μM MitoSOX, 100 nM Mitotracker Deep red and 2 μM M540.…”
Section: Methodsmentioning
confidence: 99%
“…The probes and their final concentrations were: Hoechst 33342 (H342, debris discrimination) at 5 µM; YO-PRO-1 (YP1, apoptotic changes in the plasmalemma) at 100 nM; Fluo-4 (intracellular Ca 2+ concentration assessment) at 100 nM; CM-H 2 DCFDA (CFDA, cytoplasmic ROS detection) at 5 µM; merocyanine 540 (M540, capacitation-like plasmalemma changes) at 2 µM; propidium iodide (PI, viability) at 1 µM; PNA-Alexa Fluor 647 (PNA, peanut agglutinin, acrosomal status) at 1 µg/mL; MitoTracker deep red (MT, mitochondrial activity) at 100 nM; MitoSOX (MSX, mitochondrial superoxide production) at 1 µM. These probes have been described and used by our group previously [71][72][73]. The probes were combined in TALP-HEPES as H342/Fluo-4/M540/PI/PNA, H342/CFDA/PI, H342/YP/MSX/MT.…”
Section: Flow Cytometry Analysis Of Sperm Physiologymentioning
confidence: 99%